The Impact of the Financial Crisis on the Possibility of Introducing Fiscal Federalism in the Euro Area - Kawalec, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The economic and monetary union is undergoing crisis, one triggered by both internal and external factors. The problems that arose as a result of macroeconomic shock brought the monetary union’s structural flaws to the fore. The purpose of this article is to determine if a stable monetary union is possible without a fiscal union and how the financial crisis has affected the possibility of fiscal federalism in the euro area. The problem of the euro area was tackled in the context of the economic crisis and will highlight the main problems of the monetary union and the management of the financial crisis in the EU. An analysis of the institutional arrangements introduced as a result of emerging problems in achieving nominal convergence in the euro area and budgetary imbalances arising from the global financial crisis was also examined. These solutions can in the long term form the basis for the creation of a fiscal union within the euro area.